2021
DOI: 10.1093/humrep/deab123
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptomic changes occur in uterine fluid-derived extracellular vesicles during the endometrial window for embryo implantation

Abstract: STUDY QUESTION Are uterine fluid-derived extracellular vesicles (UF-EVs) a ‘liquid biopsy’ reservoir of biomarkers for real-time monitoring of endometrial status? SUMMARY ANSWER The transcriptomic cargo of UF-EVs reflects the RNA profile of the endometrial tissue as well as changes between the non-receptive and the receptive phase, possibly supporting its use for a novel endometrial receptivity test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…Only one study could be found which analyzed mRNAs in uEVs. This study in humans identified DA mRNAs during the window of implantation (WOI) 42 . Of the 525 DA mRNAs identified in our study, an overlap of 407 with the mRNAs in human uEVs was found.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study could be found which analyzed mRNAs in uEVs. This study in humans identified DA mRNAs during the window of implantation (WOI) 42 . Of the 525 DA mRNAs identified in our study, an overlap of 407 with the mRNAs in human uEVs was found.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to exosome formation, the secretion of microvesicles requires the lipid microdomains at the membrane and a reorganization of the actin-myosin cytoskeletal network [97,98]. A possible association between the EV quantity in the spent culture media and embryo quality and competence has been suggested [99][100][101]. Specifically, fewer EVs have been reported in spent culture media of embryos leading to successful pregnancy than in those who failed, suggesting that a good quality and competent embryo releases different amounts/types of EVs compared to a low-quality embryo [102][103][104][105].…”
Section: Extracellular Vesicle Formationmentioning
confidence: 99%
“…Extracellular vesicles (EVs) have been described as an extraordinary tool for future applications in both diagnosis and therapy [91]. Owing to their high delivery efficiency, biocompatibility and multifunctional properties, EVs are expected to become a new means of drug delivery, disease diagnosis, immunotherapy and precise treatment.…”
Section: The Extracellular Vesicle Cargo As Therapeutic Targetmentioning
confidence: 99%